Effects of application methods and dose rates of carbofuranon the control of maize infesting stemborers and consequences on agronomic, yield and yield parameters in central Sudan - Abdalla, Tag Elsir E.; Zein, Mahadi M.; Mohamed, Abdelrahman A.; Omer, Ismail S. (Gezira Journal of Agricultural Science; Vol 14 No 1 (2016), 2018)
This study was conducted at Gezira (GRS) and Sennar Research Stations (SRS) farms during 2014/2015 winter season . Carbofuran was tested in form of "Carbodan 10 G®" . The application methods were : Soil dressing method (SDM) applied with the seeds at sowing , top dressing method (TDM) applied into whorls after emergence , and broadcasting method (BM) applied after emergence . The doses were 0 . 225 , 0 . 3 and 0 . 375g /hole in SDM and 5 . 85 , 7 . 8 and 9 . 75kg/fed in each of TDM and BM . Untreated control (UC) was included in the test . Stemborers damage was assessed on maize leaves and stems . Agronomic , yield and yield parameters were timely recorded . Residue analysis was performed in grains taken at milky and maturity stages . The ordered SDM , TDM and BM showed decreasing trend of dead heart by scoring 6 . 1% , 5 . 7% , and 5 . 5% at GRS , and 7 . 3% , 4 . 6% and 3 . 1% at SRS , respectively , but didn’t differ much by effects on leaves . An increasing trend in number of cobs /fed was also evident . All carbofuran treatments reduced percentage of infested plants to a range of 12 . 6%-16 . 8% vs. 22 . 4% in the UC at GRS, and 5 . 2%-15.5% vs . 30 . 5% in the UC at SRS . SDM at 0 . 375g/hole , TDM at 7 . 8 kg /fed and BM at 9 . 75 kg /fed recorded significantly lower percentage of dead heart , 3 . 7% , 3 . 8% and 3 . 6% , vs . 14 . 0% in the UC at GRS , and 9 . 3% , 2 . 4% and 4 . 5% vs . 20 . 1% in the UC at SRS , respectively . They increased plant stand , plant height , number of cobs /fed , 1000-grain weight and grain yield by 32%-105% over the UC at GRS and 46%-175% at SRS . TDM at 7 . 8 kg /fed produced 2 . 2 ton /fed which was about three times as much vs. UC (0 . 8 ton /fed) at SRS (P≤0.05) . No residue of carbofuran and its metabolites were detected in all grain samples .